Exploration of computational thinking skills: A case study of islamic senior high school students - Amrizaldi Amrizaldi; Lia Yuliati; Edi Supriana; Markus Diantoro; Lilia Halim (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to identify madrasah students' Computational Thinking (CT) skills on temperature and heat material. This research was conducted using a qualitative descriptive method using 5 CT-test essay questions to 53 grade XI IPA one of the Islamic Senior High School in Probolinggo. Data analysis techniques in research consist of 3 stages: data reduction, data presentation, and conclusions. Data analysis showed indicators of students' CT skills on a scale of 5 consisting of decomposition 3.90, recognition pattern 3.63, abstraction 2.83, and algorithm 2.37. Based on the study’s results, it can be concluded that the CT skills of the Islamic Senior High School in Probolinggo at temperature and heat are included in the medium category. Several indicators of CT skills are still challenging for students, especially in developing algorithms and abstractions. Some students need help identifying the steps to solve complex problems in understanding abstraction concepts and algorithms. In this case, practice, intensive tutoring, and student collaboration can help improve students' skills to overcome these difficulties.